Genome-wide association study identifies 18 new susceptibility variants loci associated with Brugada Syndrome. (25th November 2020) - Barc, J; Trados, R; Glinge, C; Simonet, F; Chiang, D; Jouni, M; Jurgens, S; The Brugada Syndrome Genetic Consortium, B.R.S; Tanck, M; Dina, C; Probst, V; Wilde, A; et al.
Abstract: : The Brugada Syndrome (BrS) is characterized by ST-segment elevation in the right precordial leads and is associated with an increased risk of sudden cardiac death. The disorder was initially described as a monogenic primary cardiac electrical disease. However, mutations in SCN5A, encoding the cardiac sodium channel (NaV1.5), which is the major gene associated with the disorder are found in only around 20% of cases and are associated with low penetrance. Furthermore many cases did not display familial aggregation. Based on a previous GWAS conducted on 312 BrS patients and the discovery of the unexpected strong effect of 3 common variants, we proposed that the BrS may comprise a more complex inheritance model. We conducted a genome-wide association study on 2820 individuals with BrS and 10001 ancestry-matched controls to uncover additional genetic loci that modulate susceptibility to BrS, to characterize further the BrS genetic architecture and to uncover new molecular mechanisms. We identified 21 susceptibility variants that passed the genome-wide statistical significance threshold (P<5.10–8), of which 18 were novel. Eight were located at the SCN5A-SCN10A locus, illustrating the central role of NaV1.5 in the disease. Interestingly, 9 occur in the vicinity of genes known to play a crucial role in cardiac development (HEY2, TBX20, GATA4, ZFPM2, WT1, TBX5, IRX3, IRX5) and / or control cardiac ion channel expression. Of note, 2 others signals occurred in the vicinity of microtubule / cytoskeleton associated proteins (MAPRE2 and MYO18B). Through studies in zebrafish and in human iPSC-derived cardiomyocytes, we demonstrate a role of MAPRE2 on NaV1.5 function. We identified 18 new susceptibility variants associated with BrS and uncovered a new pathophysiological molecular mechanism underlying BrS susceptibility. We provided further support for a complex genetic architecture underlying susceptibility for the disorder. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): H2020 - Marie Sklodowska Curie IF grant, Rising star grant from the Pays de la Loire regional council